Changes in the structure and function of rhizosphere soil microbial communities induced by Amaranthus palmeri invasion - Zhang, Mei; Shi, Cong; Li, Xueying; Wang, Kefan; Qiu, Zhenlu; Shi, Fuchen (Frontiers in Microbiology, 2023)
Plant invasion can profoundly alter ecosystem processes driven by microorganisms. The fundamental mechanisms linking microbial communities, functional genes, and edaphic characteristics in invaded ecosystems are, nevertheless, poorly understood. Here, soil microbial communities and functions were determined across 22 Amaranthus palmeri (A. palmeri) invaded patches by pairwise 22 native patches located in the Jing-Jin-Ji region of China using high-throughput amplicon sequencing and quantitative microbial element cycling technologies. As a result, the composition and structure of rhizosphere soil bacterial communities differed significantly between invasive and native plants according to principal coordinate analysis. A. palmeri soils exhibited higher abundance of Bacteroidetes and Nitrospirae, and lower abundance of Actinobacteria than native soils. Additionally, compared to native rhizosphere soils, A. palmeri harbored a much more complex functional gene network with higher edge numbers, average degree, and average clustering coefficient, as well as lower network distance and diameter. Furthermore, the five keystone taxa identified in A. palmeri rhizosphere soils belonged to the orders of Longimicrobiales, Kineosporiales, Armatimonadales, Rhizobiales and Myxococcales, whereas Sphingomonadales and Gemmatimonadales predominated in the native rhizosphere soils. Moreover, random forest model revealed that keystone taxa were more important indicators of soil functional attributes than edaphic variables in both A. palmeri and native rhizosphere soils. For edaphic variables, only ammonium nitrogen was a significant predictor of soil functional potentials in A. palmeri invaded ecosystems. We also found keystone taxa in A. palmeri rhizosphere soils had strong and positive correlations with functional genes compared to native soils. Our study highlighted the importance of keystone taxa as a driver of soil functioning in invaded ecosystem.